Effect of Employing Micro-Learning in an E-learning Environment on Correcting Spelling Errors Among Middle School Students - Al-Shaibani, AlJawhara Naif; Ismail, Abdellraouf Mohamed Mohamed (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to identify the most common spelling mistakes among the intermediate first-grade, and to develop the educational content model in employing micro-learning. the researcher used the quasi-experimental approach and an achievement test to measure the cognitive aspects related to correcting spelling mistakes in the Arabic language course as a tool. the study sample consisted of 40 female intermediate first grade students who were randomly selected and divided into two groups: a control group (15 students) and an experimental group (15 students), after choosing the exploratory group (10 students). the study reached a set of results, the most important of which were: there are statistically significant differences in favor of the experimental group at (α <= 0.05) in the total average scores in learning to spell among intermediate first-grade female students in Arabic (the experimental group) who learned spelling via micro-learning and (the control group) who learned by traditional method regularly in the test. the results also showed high impact of employing micro-learning in an e-learning environment to measure the cognitive and skill aspects related to correcting spelling mistakes in the Arabic language course among intermediate first-grade students. according to the results of the study, the researcher recommended several recommendations, the most important of which were: the necessity of clarifying the most common spelling mistakes and the way to correct them for female students and developing Arabic language teacher’s performance by enrolling them in training courses and qualifying them professionally.